Resolving incomplete single nucleotide polymorphism tagging of HLA‐DQ2.2 for coeliac disease genotyping using digital droplet PCR. (26th February 2018) - Hardy, M. Y.; Ontiveros, N.; Varney, M. D.; Tye‐Din, J. A.
Abstract : A hallmark of coeliac disease (CD) is the exceptionally strong genetic association with HLA‐DQ2.5, DQ8, and DQ2.2. HLA typing provides information on CD risk important to both clinicians and researchers. A method that enables simple and fast detection of all CD risk genotypes is particularly desirable for the study of large populations. Single nucleotide polymorphism (SNP)‐based HLA typing can detect the CD risk genotypes by detecting a combination of six SNPs but this approach can struggle to resolve HLA‐DQ2.2, seen in 4% of European CD patients, because of the low resolution of one negatively predicting SNP. We sought to optimise SNP‐based HLA typing by harnessing the additional resolution of digital droplet PCR to resolve HLA‐DQ2.2. Here we test this two‐step approach in an unselected sample of Mexican DNA and compare its accuracy to DNA typed using traditional exon detection. The addition of digital droplet PCR for samples requiring negative prediction of HLA‐DQ2.2 enabled HLA‐DQ2.2 to be accurately typed. This technique is a simple addition to a SNP‐based typing strategy and enables comprehensive definition of all at‐risk HLA genotypes in CD in a timely and cost‐effective manner.